Lipopolysaccharide-induced NF-kappa B activation in mouse 70Z/3 pre-B lymphocytes is inhibited by mevinolin and 5'-methylthioadenosine: roles of protein isoprenylation and carboxyl methylation reactions. - Law, R E (1992)
We show that both the lipopolysaccharide (LPS)-induced activation of NF-kappa DNA binding and kappa gene expression are blocked by treating murine pre-B lymphocyte 70Z/3 cells with 5'-methylthioadenosine (MTA), an inhibitor of several S-adenosylmethionine-dependent methylation reactions. We further show that the LPS-induced incorporation of radioactivity from [methyl-3H]methionine into methyl ester-like linkages on a group of membrane polypeptides is also inhibited by MTA treatment, suggesting the involvement of protein methylation reactions in the LPS signal transduction pathway. We also find that NF-kappa B and kappa gene activation in LPS-treated 70Z/3 cells is blocked by mevinolin, an inhibitor that prevents protein isoprenylation. Interestingly, mevinolin-treated cells also exhibited a marked reduction in the methylation of membrane proteins. Neither MTA nor mevinolin significantly inhibited NF-kappa B activation by phorbol myristate acetate, suggesting that these agents act early in signal transduction. These results provide the first evidence that carboxyl methylated and/or isoprenylated proteins play an essential role in the LPS-signaling pathway.